Circadian clock and lipid metabolism disorders: a potential therapeutic strategy for cancer - Liu, Mengsi; Zhang, Zhen; Chen, Yating; Feng, Ting; Zhou, Qing; Tian, Xuefei (Frontiers in Endocrinology, 2023)
Recent research has emphasized the interaction between the circadian clock and lipid metabolism, particularly in relation to tumors. This review aims to explore how the circadian clock regulates lipid metabolism and its impact on carcinogenesis. Specifically, targeting key enzymes involved in fatty acid synthesis (SREBP, ACLY, ACC, FASN, and SCD) has been identified as a potential strategy for cancer therapy. By disrupting these enzymes, it may be possible to inhibit tumor growth by interfering with lipid metabolism. Transcription factors, like SREBP play a significant role in regulating fatty acid synthesis which is influenced by circadian clock genes such as BMAL1, REV-ERB and DEC. This suggests a strong connection between fatty acid synthesis and the circadian clock. Therefore, successful combination therapy should target fatty acid synthesis in addition to considering the timing and duration of drug use.Ultimately, personalized chronotherapy can enhance drug efficacy in cancer treatment and achieve treatment goals.